Random Key Cuckoo Search for the Quadratic Assignment Problem - Ouaarab, Aziz; Ahiod, Belaid; Yang, Xin-She (Transactions on Engineering and Computing Sciences, 2017)
This paper proposes an adaptation of the Random- Key Cuckoo Search (RKCS) algorithm for solving the famous Quadratic Assignment Problem (QAP). We used a simplified and efficient random-key encoding scheme to convert a continous space (real numbers) into a combinatorial space. We also consid- ered the displacement of a solution in both spaces by using Le´vy flights. The performance of the RKCS for QAP is tested against a set of benchmarks of QAP from the well-known QAPLIB library, and the comparison with a set of other methaheuristics is also carried out.